Depression and anxiety in patients from Lebanon with new onset functional seizures - Nawfal, Omar (2021)
Objectives To prospectively compare the frequencies of depression and anxiety in patients with new onset functional seizures versus two age and gender-matched control groups consisting of patients with new onset epileptic seizures and normal individuals. Methods Consecutive patients, 16 years and older, enrolled in a prospective study for suspected new onset epileptic seizures and diagnosed with documented functional seizures were included. We compared the depression and state and trait anxiety scores using the Beck Depression Inventory (BDI) and the State Trait Anxiety Inventory (STAI) between patients with functional seizures and the other two control groups. Results The 33 patients with functional seizures had significantly higher depression and anxiety scores compared to those with epileptic seizures and normal controls. Twenty patients (60.6%) in the functional seizures group scored in the “depression” range compared to 5/33 (15.2%) in the epileptic seizures and 1/33 (3%) in the control groups. In the functional seizures group, 14/33 (42.4%) had scores in the “state anxiety” range compared to 6/33 (18.2%) and 2/33 (6.1%) in the epileptic seizures and normal control groups, respectively. Similarly, 15/33 (51.5%) of patients in the functional seizures group had scores in the “trait anxiety” range compared to 4/33 (12.1%) and 1/33 (3%) in the epileptic seizures and normal control groups, respectively. Conclusions Our results indicate that patients with new onset functional seizures frequently suffer from depression and anxiety at the time of their initial evaluation. These findings underscore the importance of screening for depression and anxiety in that patient population.